Obstetric complications in maternal deaths related to AIDS - Venter, Berna (My University, 2009)
ABSTRACT Objectives: To determine what obstetric complications can be associated with end-stage AIDS and maternal death. Method: From 1990 to 2005 the maternal death files of patients with either AIDS-defining illnesses or CD4 counts of less than 200x106/ℓ were analyzed in a descriptive study. All patients died undelivered or within 42 days of delivery. Result: Sixty six percent (49/74) of pregnancies ended prematurely by preterm delivery or miscarriage. Twenty perinatal deaths occurred. The average birth weight was 1498g at an average gestational age of 30.5 weeks. The mean CD4 count was 45.5x106/ℓ. The majority of maternal deaths were caused by respiratory illnesses. Conclusion: Preterm ABSTRACT Objectives: To determine what obstetric complications can be associated with end-stage AIDS and maternal death. Method: From 1990 to 2005 the maternal death files of patients with either AIDS-defining illnesses or CD4 counts of less than 200x106/ℓ were analyzed in a descriptive study. All patients died undelivered or within 42 days of delivery. Result: Sixty six percent (49/74) of pregnancies ended prematurely by preterm delivery or miscarriage. Twenty perinatal deaths occurred. The average birth weight was 1498g at an average gestational age of 30.5 weeks. The mean CD4 count was 45.5x106/ℓ. The majority of maternal deaths were caused by respiratory illnesses. Conclusion: Preterm labour and early pregnancy loss are common among terminally ill pregnant women with AIDS. It is proposed that hypoxia in the presence of respiratory disease could lead to cytokine production in the uterine cavity, leading to preterm delivery, even in the absence of intrauterine infection.
Keywords: AIDS; maternal deaths; South Africa; obstetric complications